Analisis Strategi Manajemen Sarana dan Prasarana dalam Mendukung Kegiatan Belajar Mengajar (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to analyze the management of educational facilities and infrastructure at UPT SMP Negeri 37 Medan through interviews and direct observation. The research findings indicate that the school provides generally adequate facilities that support the learning process, yet several aspects still require improvement, particularly in toilet cleanliness, equitable distribution of technological tools, library utilization, and the maintenance of green open spaces. Classroom facilities, sports areas, the computer laboratory, and the UKS room are available and functioning, although their use has not been maximized. The study also found that the absence of CCTV and inconsistent cleaning routines hinder optimal facility management. Based on the analysis, well-managed facilities significantly contribute to creating a conducive learning environment, improving student motivation, and supporting innovative learning methods. Therefore, continuous and systematic management of facilities and infrastructure is essential to enhance the overall quality of education in the school.